Claiming spaces for acts of citizenship: recent experiences of activists in Morocco - Sylvia I. Bergh (Edward Elgar Publishing, 2018)
Since October 2016 and starting in the northern Rif region, Morocco has witnessed popular protests fuelled by a widespread sense of hogra, i.e. deprivation of dignity due to nepotism, corruption and marginalisation. These protests can be considered a revival of the spirit of the February 20 Movement (F20M) of 2011, which led to the adoption of a new Constitution. Based on interviews with activists in Rabat, Casablanca and Tangier, this chapter addresses the following questions: How did these activists keep the spirit of the F20M alive? How are their 'acts of citizenship' (Engin Isin) helping them to claim public spaces? How do they understand the concept of citizenship as compared to how it is used in the state's discourse? What are the state's reactions to their activities, and how do the groups in turn respond to them? Finally, what, if anything, does the 2011 Constitution mean to these activists?